2016
DOI: 10.2147/opth.s89561
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the safety and efficacy of bimatoprost for eyelash growth in pediatric subjects

Abstract: PurposeEvaluate the safety and effectiveness of bimatoprost 0.03% for treatment of eyelash hypotrichosis in a pediatric population.Patients and methodsThis multicenter, randomized, double-masked, parallel-group study was conducted at seven sites in the US and Brazil. Subjects with eyelash hypotrichosis caused by chemotherapy or alopecia areata (aged 5–17 years) or healthy adolescents aged 15–17 years were enrolled (N=71). Subjects applied bimatoprost 0.03% or vehicle to upper eyelid margins once nightly for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Bimatoprost was hypothesized to boost eyelash growth by activating prostamide-sensitive receptors related to HFs. This enhances the conversion of the follicle from the telogen phase of the hair cycle to the anagen phase and increases the duration of the anagen phase, 25,26 leading to increased hair thickness due to dermal papillae enlargement. 27 Regarding dermoscopic findings in the present study, broken In the present study, vellus hair showed a significant increase in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bimatoprost was hypothesized to boost eyelash growth by activating prostamide-sensitive receptors related to HFs. This enhances the conversion of the follicle from the telogen phase of the hair cycle to the anagen phase and increases the duration of the anagen phase, 25,26 leading to increased hair thickness due to dermal papillae enlargement. 27 Regarding dermoscopic findings in the present study, broken In the present study, vellus hair showed a significant increase in all groups.…”
Section: Discussionmentioning
confidence: 99%
“… 94 , 95 Some studies have assessed the drug in adult and pediatric patients, with variable results, which is probably due to conditions with different severities and, therefore, different AA prognoses. 96 It appears to be a safe and potentially effective agent for treating the region. It is important to note the risk of eyelid hyperpigmentation and darkening of the iris.…”
Section: Pre-treatment Considerationsmentioning
confidence: 99%
“…The subgroup analysis of the dose was performed in each group ( Figure 5 ), with 0.05 mL of experimental group reagent in all four experimental groups ( 35 , 37 , 39 , 40 ), 0.25 mL of reagent in one experimental group ( 38 ), and 1.0 mL of reagent in one experimental group ( 36 ). The results showed that the dose of the 1.0 mL group had the largest effect size [SMD = 7.30, 95% CI (6.06, 8.54), p < 0.00001; Figure 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was 1 study with unknown adverse reactions ( 36 ). The remaining studies ( 35 , 38 , 40 ) reported local adverse reactions to drug administration, including conjunctival hyperemia, punctate keratitis, erythema, folliculitis, the sensation of bilateral burning, and application site pruritus. There were also rare side effects reported by enrolled studies, such as urinary tract infections, other body hair increase, influenza and actinic keratosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation